Determinants of food insecurity among elderly people: findings from the Canadian Community Health Survey. Issue 9 (22nd September 2022) - Kansanga, Moses Mosonsieyiri; Sano, Yujiro; Bayor, Isaac; Braimah, Joseph Asumah; Nunbogu, Abraham Marshall; Luginaah, Isaac
Abstract: Food insecurity among elderly people is a major public health concern due to its association with several health conditions. Despite growing research and implementation of diverse income-based policy measures, food insecurity among elderly people remains a major policy issue in Canada. Additional research could inform food policy beyond strategies that target improving the financial resources of elderly people. Drawing data from the Canadian Community Health Survey (N = 24, 930), we explored the correlates of food insecurity among older adults using negative log-log logistic regression techniques. Our findings show that certain categories of elderly people are more prone to food insecurity. These segments include seniors who are visible minorities (OR = 1.29, p < 0.01), live alone (OR = 1.13, p < 0.05), have a very weak sense of community belonging (OR = 1.40, p < 0.001), in poor physical health (OR = 1.20, p < 0.01), and those in lower age and income categories. These findings corroborate previous studies that demonstrate that food insecurity among elderly people is a complex phenomenon influenced by diverse socio-economic factors. In Canada, food security policies targeted at elderly people have largely prioritised poverty alleviation through income support programmes. While these programmes can improve the purchasing power of elderly people, they may not be sufficient in ensuring food security. There is a need to embrace and further investigate an integrated approach that pays attention to other contextual socio-economic dynamics.